Fairness-Aware Radio Resource Management in OFDMA-Based Wimax Networks with Comparison Between Three Downlink Scheduling Algorithms - Osama Shibani,; Arebi Yakhlef,; Alsbani, Ayoub Alazzabi (AlQalam Journal of Medical and Applied Sciences, 2024)
This study focuses on managing equity-conscious radio resources in OFDMA-based WIMAX networks with comparison of three algorithms, Max Rate, RR and PFS. Hence WiMAX Forum has been formed, which promotes the technology and provides compatibility and teroperability for 802.16-based products. The problem in heterogeneous WiMAX, users may possess different transmit power capabilities and experience independent channel realizations. As a result, those with lower power Capabilities or poor channel conditions will starve throughput share. It is observed that users with better channel conditions always dominate usage of the spectrum, causing low throughput for users with poor channel conditions. This paper studied the performance of downlink scheduling algorithms that perform radio resource allocation in order to improve the performance of the WiMAX system. These algorithms are Max Rate, Round Robin, and Proportional Fair. In addition, scheduling algorithm was implementing in order to explain the fairness concept. The algorithms were comparing to each other in terms of system throughput and fairness index. The performance evaluations are carrying out using MATLAB software. Simultaneous results show that the most suitable scheduling algorithm in terms of fairness index and system throughput for the WiMAX network is proportional fair. Meanwhile, Max Rate provides the highest throughput, even though the number of users is increased.